Antidepressant adherence among outpatients with major depressive disorder - Ali Omar Yassen; Nasraw Mustafa Mahmud; Aya Diyar Bilal; Mohd Shahezwan Abd Wahab (Pensoft Publishers, 2024)
Major Depressive Disorder (MDD) is a global mental health concern, with treatment often involving antidepressant (AD) medications. However, adherence to these medications remains a significant challenge. This study aims to investigate the factors influencing medication adherence among individuals with MDD in Erbil, Iraq. This study was conducted at Erbil Psychiatric Hospital, a leading mental healthcare facility in Erbil city. Participants aged 18 to 65, diagnosed with MDD as per the DSM-5 criteria, were treated with antidepressants. The recruitment of 106 participants was facilitated by their treating psychiatrists at the hospital. Data analysis was conducted using SPSS version 22, standard for social science research. Out of the 106 participants, 64.2% were females, and 35.8% were males. The largest age group was 35-45, comprising 33% of the sample. A vast majority (99.1%) were under regular follow-up, with only 0.9% experiencing relapse. The primary antidepressant used was selective serotonin reuptake inhibitors (SSRIs) (72.6%). Most participants (61.3%) reported very high medication adherence. The notable barriers included treatment duration (13.4%), forgetting to take antidepressants (11.9%), frequent medication refills (17.9%), cultural and religious beliefs (19.3%), stigma (19.3%), travelling issues (42.9%), and lack of hospitals and clinics (30.8%). Healthcare facilitators such as effectiveness of antidepressants (27.5%), patient-provider relationship such as trusting healthcare providers (50.7%), and reminders such as keeping pills in visible places (65.9%) were prominent facilitators aiding adherence. Future research should focus on culturally tailored interventions and collaborative efforts among stakeholders. By addressing socio-cultural nuances and enhancing mental health support, more effective strategies can be developed to tackle medication adherence challenges in Erbil's unique context.